2016
DOI: 10.15252/embj.201593518
|View full text |Cite
|
Sign up to set email alerts
|

Novel function of Tau in regulating the effects of external stimuli on adult hippocampal neurogenesis

Abstract: Tau is a microtubule‐associated neuronal protein found mainly in axons. However, its presence in dendrites and dendritic spines is particularly relevant due to its involvement in synaptic plasticity and neurodegeneration. Here, we show that Tau plays a novel in vivo role in the morphological and synaptic maturation of newborn hippocampal granule neurons under basal conditions. Furthermore, we reveal that Tau is involved in the selective cell death of immature granule neurons caused by acute stress. Also, Tau d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
104
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(114 citation statements)
references
References 68 publications
8
104
1
1
Order By: Relevance
“…However, this aggregation of Tau compromises its microtubulestabilising functions (loss of physiological function), favoring the evolution of the pathology. In agreement with the loss-of-function model, we have reported behavioral changes and neurogenesis in aged Tau knockout mice (53). Interestingly, EMT genes are enriched in the affected areas of AD brains (54).…”
Section: Tau Expression Is a Surrogate Marker Of The Less Aggressive supporting
confidence: 83%
“…However, this aggregation of Tau compromises its microtubulestabilising functions (loss of physiological function), favoring the evolution of the pathology. In agreement with the loss-of-function model, we have reported behavioral changes and neurogenesis in aged Tau knockout mice (53). Interestingly, EMT genes are enriched in the affected areas of AD brains (54).…”
Section: Tau Expression Is a Surrogate Marker Of The Less Aggressive supporting
confidence: 83%
“…For example, prolonged exposure to stress or high levels of GC trigger Tau accumulation and hyperphosphorylation accompanied by synaptic missorting of Tau and neuronal atrophy (Green et al, 2006;Sotiropoulos et al, 2011;Pinheiro et al, 2015;Lopes et al, 2016c). Importantly, Tau is essential for this stress/GC-driven damage, as Tau ablation was found to be neuroprotective (Lopes et al, 2016c;Pallas-Bazarra et al, 2016;Dioli et al, 2017). While previous in vitro studies showed that GC reduce Tau turnover (Sotiropoulos et al, 2008a), the underlying molecular mechanisms were unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, emerging studies support a crucial role for Tau in diverse brain pathologies (for review, see Sotiropoulos et al, ) including prolonged exposure to stressful conditions, a known risk factor for AD and major depressive disorder (Vyas et al , ). In particular, recent studies demonstrate that exposure to chronic environmental stress or the major stress hormones, glucocorticoids (GC), triggers the accumulation of Tau and its synaptic missorting, precipitating dendritic atrophy and synaptic dysfunction in a Tau‐dependent manner (Pinheiro et al , ; Lopes et al , ,b; Pallas‐Bazarra et al , ; Dioli et al , ). However, the cellular mechanisms responsible for stress/GC‐induced accumulation of Tau remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…For example, prolonged exposure to stress or high levels of GC trigger Tau accumulation and hyperphosphorylation, accompanied by synaptic missorting of Tau and neuronal atrophy (Green et al, 2006, Lopes et al, 2016c, Pinheiro et al, 2015, Sotiropoulos et al, 2011. Importantly, Tau is essential for this stress/GC-driven damage, as Tau ablation was found to be neuroprotective (Dioli et al, 2017, Lopes et al, 2016c, Pallas-Bazarra et al, 2016. While previous in vitro studies showed that GC reduce Tau turnover , the underlying molecular mechanisms were unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, emerging studies support a crucial role for Tau in diverse brain pathologies (for review, see 8 ) including prolonged exposure to stressful conditions, a known risk factor for AD and major depressive disorder 9 . In particular, recent studies demonstrate that exposure to chronic environmental stress or the major stress hormones, glucocorticoids (GC), triggers the accumulation of Tau and its synaptic missorting, precipitating dendritic atrophy and synaptic dysfunction in a Tau-dependent manner [10][11][12][13][14] . However, the cellular mechanisms responsible for stress/GC-induced accumulation of Tau remain unclear.…”
Section: Introductionmentioning
confidence: 99%